Vaginal and Labial Graft Urethroplasty in Female Urethral Stricture: A Systematic Review - Nur Syifa Fara Wahida Purba; Quranayati Quranayati (GLOBAL HEALTH SCIENCE GROUP, 2026)
Female urethral stricture is considered a relatively uncommon clinical condition, and urethral dilatation has traditionally been the preferred treatment. In recent years, various reconstructive surgical techniques have emerged to provide more definitive management for this challenging group of patients, including the use of grafts in urethroplasty. This study aimed to review the use of vaginal and labial grafts in urethroplasty for female urethral stricture. A systematic review was conducted using PubMed and related databases to identify studies published between 2014 and April 2025. The results were classified according to surgical technique and type of graft used in augmentation urethroplasty. A total of seven studies involving 119 patients were included. The mean follow-up period was 13.55 months for labial grafts and 17.23 months for vaginal wall grafts. Labial grafts demonstrated slightly higher success rates (84%) compared to vaginal grafts (81.73%). In the vaginal graft group, incontinence and recurrence were reported in 17.5% of cases, while failed calibration occurred in 3.8% of patients in the labial graft group. No major donor-site complications were reported. Overall, both graft types provide feasible and safe options for managing female urethral stricture, with labial grafts showing slightly better outcomes.